Supporting the Management of Spontaneous Volunteers Through AI-generated Task Descriptions - Klafft, Michael (Proceedings of the International ISCRAM Conference, 2025)
Since about 2015, smartphones apps have been used in some areas of Germany to coordinate first responders in case of emergencies, and crises. Initially, the focus of such applications were medical emergencies and sudden cardiac arrests in particular. Later, use cases for crowdtasking apps have been broadened in order to address all types of disaster scenarios, and tasks. Additionally, disaster and emergency managers use such tools nowadays to coordinate untrained, spontaneous volunteers without specific qualifications in times of crises. While those volunteers can be of valuable support for some disaster management tasks, such as establishing emergency shelters, emergency management professionals have sometimes perceived the management of spontaneous helpers as burdensome in stressful situations. Furthermore, in times of crises, some emergency managers also felt overwhelmed by the situation and would have needed more guidance. Artificial intelligence could provide tools and features to support emergency managers in the process of managing spontaneous volunteers. This paper presents some initial results from a desktop exercise where generative AI was used to support the creation of task descriptions for spontaneous volunteers, and discusses future uses of AI with regard to volunteer management in disaster situations.